The Importance of Disability Research (2015)
Why is disability research important? When asked this question I tend to respond by revising it in my head (if not out loud). Why is disability research so important? Why is any research important? I might go on in this vein but my point is that disability research has the potential to improve understandings of the most fundamental aspect of the human condition —namely, the diversity of minds and bodies. Whatever our history, geography, class, gender, ethnicity, sexuality, and/or religion, we have, have had, and/or will have a profoundly intimate relationship with disability. It is, after all, via the very diversity of minds and bodies that we are ultimately unified.